COMPARISON PERFORMANCE OF WORD2VEC, GLOVE, FASTTEXT USING SUPPORT VECTOR MACHINE METHOD FOR SENTIMENT ANALYSIS - Anjani, Margaretha; Irmanda, Helena Nurramdhani (Informatika, Universitas Jenderal Soedirman, 2024)
Spotify is a digital audio service that provides music and podcasts. Reviews received by the application can affect users who will download the application. The unstructured characteristic of review text is a challenge in text processing. To produce a valid sentiment analysis, word embedding is required. The data set that is owned is divided by a ratio of 80:20 for training data and testing data. The method used for feature expansion is Word2Vec, GloVe, and FastText and the method used in classification is Support Vector Machine (SVM). The three word embedding methods were chosen because they can capture semantic, syntactic, and contextual meanings around words when compared to traditional engineering features such as Bag of Word. The best performance evaluation results show that the GloVe model produces the best performance compared to other word embeddings with an accuracy value of 85%, a precision value of 90%, a recall value of 79%, and an f1-score of 85%.